In situ differentiation of labile/inert metal species in Brazilian tropical rivers by means of a time-controlled batch-procedure based on TEPHA resin - Goveia, Danielle [UNESP]; Lobo, Fabiana A. [UNESP]; Bellin, Iramaia C.; Fraceto, Leonardo F. [UNESP]; Menegario, Amauri A. [UNESP]; Burba, Peter; Rosa, Andre H. [UNESP] (Taylor & Francis Ltd, 2011)
The present study deals with a new analytical procedure based on a cellulose diffusion membrane and immobilised tetraethylene-pentamine-hexaacetate chelator (DM-TEPHA) for an in situ differentiation of labile and inert metal species in aquatic systems. The DM-TEPHA system was prepared by placing TEPHA chelator in pre-purified cellulose bags and in situ applied immersing the system in two Brazilian rivers to study the relative lability of metal species (Cu, Pb, Fe, Mn and Ni) as a function of the time and the quantity of exchanger, respectively. The procedure is simple and enables a new perspective for understanding the complexation, transport, stability and lability of metal species in aquatic systems rich in organic matter.
Keywords: water; humic substances; lability, metals; aquatic organic matter